Late management of the aortic root after repair of tetralogy of Fallot: A European multicentre study. Issue 1 (5th November 2019) - Vida, Vladimiro L.; Triglia, Laura Torlai; Zanotto, Lorenza; Zanotto, Lucia; Bertelli, Francesco; Padalino, Massimo; Sarris, George; Protopapas, Eleftherios; Prospero, Carol; Pizarro, Christian; Cleuziou, Julie; Myers, Patrick O.; et al.
Abstract: Objectives: We sought to determine the indications, type, and outcomes of reoperations on the aortic root after repair of tetralogy of Fallot (TOF). Methods: Eleven centers belonging to the European Congenital Heart Surgeons Association contributed to the data collection process. We included 36 patients who underwent surgical procedures on the aortic root, including surgery on the aortic valve and ascending aorta, between January 1975 and December 2017. Original diagnoses included TOF‐pulmonary stenosis (n = 18) and TOF‐pulmonary atresia (n = 18). The main indications for reoperation were aortic insufficiency (n = 19, 53%), aortic insufficiency and dilatation of the ascending aorta (n = 10, 28%), aortic root dilatation (n = 4, 11%), and ascending aorta dilatation (n = 3, 8%). Results: The median age at reoperation was 30.4 years (interquartile range 20.3‐45.3 years), and mechanical aortic valve replacement was the most common procedure performed. Five patients died early after reoperation (14%), and larger ascending aorta diameters were associated with early mortality ( P  = .04). The median age at the last follow‐up was 41.4 years (interquartile range 24.5‐51.6 years). Late death occurred in five patients (5/31, 16%). Most survivors (15/26, 58%) were asymptomatic at the last clinical examination (New York Heart Association, NYHA class I). The remaining patients were NYHA class II (n = 7) and III (n = 3). The most common symptoms were fatigue (n = 5), dyspnea (n = 4), and exercise intolerance (n = 3). Conclusions: Reoperations on the aortic root are infrequent but may become necessary late after TOF repair. The main indications for reoperation are aortic insufficiency, either isolated or associated with a dilatation of the ascending aorta. The surgical risk at reoperation was high and the presence of ascending aorta dilation is related to higher mortality.